Effect of College Students’ Academic Stress on Anxiety Under the Background of the Normalization of COVID-19 Pandemic: The Mediating and Moderating Effects of Psychological Capital - Yang, Yong; Yang, Pingzhan (Frontiers in Psychology, 2022)
Based on the background of the continuous development of COVID-19 pandemic, the effect of academic stress on anxiety of college students, as well as the mediating and moderating role of psychological capital are discussed, so as to provide intervention measures for reducing the academic stress and anxiety level of college students during the pandemic. The study used the Academic Stress Scale, the Psychological Capital Scale and the Anxiety Scale to conduct a questionnaire survey on 280 college students in 5 colleges and universities in Northern Hunan, and obtained 229 valid questionnaires. The data analysis results show that there are differences in academic stress between different genders, and differences in the variable of psychological capital among college students of different grades; Whether he is a student leader and whether he has won a scholarship, the difference of this factor in the three variables of academic stress, psychological capital and anxiety.is not statistically significant. The results of this study showed that psychological capital significantly negatively predicted anxiety (β=-0.602, t=-9.702, p<0.001), academic stress significantly positively predicted anxiety (β=0.247, t=5.462, p<0.001), psychological capital played a partial mediating role between academic stress and anxiety, and psychological capital also had a certain moderating role between academic stress and anxiety (β=-0.15, t=-4.51, p<0.001). The conclusion of the study is that in the context of the continuous development of COVID-19 pandemic, positive psychological capital can effectively reduce the anxiety caused by academic stress. This result suggests that the positive psychological capital state of college students should be improved, which can effectively relieve pressure and reduce anxiety.